Alternative sugar substitutes in canned cherries with improved nutritional value suitable for special diet consumers - Maldonado, Mariela (2014)
Cherries in syrup were developed with an improved nutritional profile, which can be a healthier choice for people with special diets by the partial and total replacement of sucrose with less caloric polyols as alternative. The tests performed on Bing cherries were: Witness: sucrose 100%, T1: sucrose-maltitol: 50-50%, T2: sucrose-erythritol-maltitol: 20-30-50%, T3: maltitol-erythritol-mannitol: 55-30-15%. The candied cherries reached a 55°Brix for all formulations, which were colored with erythrosine and amaranth. Cherries were packaged and sterilized. A similar behavior was observed in all formulations, regarding the evolution of Brix, pH and density of syrups. The sucrose replacement with polyols had a significant effect (α = 0.05) in reducing shear stress and aw in the finished product when sucrose was replaced by polyol formulations tested with respect to the witness with 100% sucrose. Color, showed significant differences (α = 0.05). The T2 formulation reached higher values of lightness, close to red and yellow, being correlated with the results of sensory evaluation. Sensorily, T2 formulation had greater acceptance than the Witness, with 43% preference. According to Art. 535 of Argentine Food Code (1971), the T1 formulation, can be classified as a "low in sugar" food; T2 formulation, as a "reduced caloric value" and "low in sugar" food; while the T3 formulation, as "reduced caloric value" and "no added sugars".